Legal education as a measure to prevent sexual assault against minors - Huerta Molina, John Franck (2022)
In the middle of the 21st century it is unimaginable that citizens can live outside the law, especially criminal law; however, as a paradigm, in certain cities of Peru it is usual to start a common-law union and a family with 14-year old minors. This assertion is not only notable for the news, but also for the criminal proceedings that are exposed in the judiciary, since this practice qualifies as a crime of sexual assault against minors, a subject that has been discussed arduously and recently in the Peruvian criminal jurisprudence. According to the above, if the aforementioned legal issue was discussed by experts in the last decade, how could the population be required to know about its prohibition and its criminal consequences? The greater number of persons prosecuted for sexual assault against minors alleges ignorance of its prohibition. However, this is an issue that, when brought to a criminal trial, requires a correct application of the criminal description, the parameters established by the Supreme Court of Justice, and qualified evidence in order not to generate impunity. In this line of ideas, it is necessary to try to understand if the factor of ignorance can be counteracted by the provision of a legal education containing basic information on criminal law and thus achieve mitigation in the incidence of the crime of sexual assault against minors.